2008
DOI: 10.1186/1471-2105-9-s12-s16
|View full text |Cite
|
Sign up to set email alerts
|

Predicted mouse peroxisome-targeted proteins and their actual subcellular locations

Abstract: BackgroundThe import of most intraperoxisomal proteins is mediated by peroxisome targeting signals at their C-termini (PTS1) or N-terminal regions (PTS2). Both signals have been integrated in subcellular location prediction programs. However their present performance, particularly of PTS2-targeting did not seem fitting for large-scale screening of sequences.ResultsWe modified an earlier reported PTS1 screening method to identify PTS2-containing mouse candidates using a combination of computational and manual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Nevertheless, results obtained in the past few years from various bioinformatics studies and proteome analyses of isolated peroxisomes have revealed that the PTS1 is far more diverse and complex than just a C‐terminal SKL tripeptide motif (Brocard and Hartig 2006; Mizuno et al 2008; Palma et al 2009; Ghosh and Berg 2010; Reumann 2011). For instance, in a recent survey of all known Arabidopsis peroxisomal proteins, as well as their putative orthologs and homologous ESTs from other diverse plant species, over 23 new PTS1 tripeptides were identified, many of which possessed amino acid residues that differ considerably from those originally defined by the SKL motif (Lingner et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, results obtained in the past few years from various bioinformatics studies and proteome analyses of isolated peroxisomes have revealed that the PTS1 is far more diverse and complex than just a C‐terminal SKL tripeptide motif (Brocard and Hartig 2006; Mizuno et al 2008; Palma et al 2009; Ghosh and Berg 2010; Reumann 2011). For instance, in a recent survey of all known Arabidopsis peroxisomal proteins, as well as their putative orthologs and homologous ESTs from other diverse plant species, over 23 new PTS1 tripeptides were identified, many of which possessed amino acid residues that differ considerably from those originally defined by the SKL motif (Lingner et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, most, if not all, PTS1‐containing proteins, especially those that possess non‐canonical PTS1, appear to rely on so‐called ‘accessory’ or ‘auxiliary’ residues that lie just upstream of their C termini and function to contextually enhance the efficiency of peroxisomal targeting (Brocard and Hartig 2006). There is also growing appreciation that changes in the overall conformation of a protein, for instance, in response to a certain cellular cue, can influence the accessibility of its PTS1; hence, a protein that contains a PTS1 that, on its own is sufficient for targeting to peroxisomes, may in some cases be localized to the cytosol or some other subcellular compartment (Eisenhaber and Eisenhaber 2007; Mizuno et al 2008; Reumann 2011). Taken together, this means that the current criteria by which a C‐terminal tripeptide is predicted and/or experimentally confirmed to be a bona fide PTS1 must take into consideration not only the ever‐expanding flexibility of functional residues within the PTS1 tripeptide motif, but also the structural/sequence‐related context in which the tripeptide normally exists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the presence of a canonical PTS2 motif is not necessary suYcient to target the protein to peroxisome. Indeed, Mizuno et al (2008) showed that of Wve mouse proteins containing conserved PTS2 motifs identiWed by bioinformatic approaches, none located to peroxisome. The authors pointed out the poor performance of computer-aided predictions of PTS2-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…APE1 contains dual targeting signals and preferentially resides in the nuclei with conditional distribution in the mitochondria. Conditional subcellular sorting was also found for the PTS, where it may oscillate from silent to functional depending on its surface accessibility (Dinur-Mills et al, 2008;Mizuno et al, 2008). Similar to the NRDR protein, which harbors a putative MTS and PTS (Fig.…”
Section: Discussionmentioning
confidence: 91%